Comparing omeprazole with fluoxetine for treatment of patients with heartburn and normal endoscopy who failed once daily proton pump inhibitors: Double‐blind placebo‐controlled trial. Issue 5 (7th February 2014) - Ostovaneh, M. R.; Saeidi, B.; Hajifathalian, K.; Farrokhi‐Khajeh‐Pasha, Y.; Fotouhi, A.; Mirbagheri, S. S.; Emami, H.; Barzin, G.; Mirbagheri, S. A.
Abstract Background Patients with heartburn but without esophageal erosion respond less well to proton pump inhibitors (PPIs). There is a growing body of evidence implicating the role of psychological comorbidities in producing reflux symptoms. Pain modulators improve symptoms in patients with other functional gastrointestinal disorders. We aimed to compare the efficacy of fluoxetine with omeprazole and placebo to achieve symptomatic relief in patients with heartburn and normal endoscopy who failed once daily PPIs. Methods Endoscopy‐negative patients with heartburn who failed once daily PPIs were randomly allocated to receive 6 weeks treatment of fluoxetine, omeprazole, or placebo. Random allocation was stratified according to ambulatory pH monitoring study. Percentage of heartburn‐free days and symptom severity was assessed. Key Results Sixty patients with abnormal and 84 patients with normal pH test were randomized. Subjects receiving fluoxetine experienced more improvement in percentage of heartburn‐free days (median 35.7, IQR 21.4–57.1) than those on omeprazole (median 7.14, IQR 0–50, p < 0.001) or placebo (median 7.14, IQR 0–33.6, p < 0.001). In normal pH subgroup, fluoxetine was superior to both omeprazole and placebo regarding percentage of heartburn‐free days (median improvement, 57.1, IQR 35.7–57.1 vs 13.9, IQR, 0–45.6 and 7.14, 0–23.8, respectively, p < 0.001), but no significant difference was observed between medications in abnormal pH subgroup. Conclusions & Inferences Fluoxetine was superior to omeprazole for improving the symptoms of patients with heartburn and normal endoscopy who failed once daily PPIs. The superiority of fluoxetine was mostly attributed to those with normal esophageal pH rather than those with abnormal pH (ClinicalTrials.gov, number NCT01269788).